Potencial turístico del cantón Salcedo. - Quinatoa Vinocunga, María José (2023)
Salcedo canton belongs to the province of Cotopaxi, is characterized by its population that is dedicated to of livestock and agriculture activities. It is important to highlight that this canton has natural and cultural attractions, with characteristics that attract the attention of visitors, helping to generate a new source of economic income for its inhabitants through tourism development. However, there is little knowledge of the existing tourist attractions in the canton and little appreciation of them by the local population. In this context, the general objective of the research is "To determine the potential of the Salcedo canton in the province of Cotopaxi for the proposal of an academic article". The research has a qualitative methodological approach since it focuses on the interpretation of reality, the study of human actions and social life, with the purpose of knowing natural and cultural aspects of the Salcedo canton. For its development, three specific objectives were proposed. The first objective consists of updating the inventory of the cultural and natural tourist attractions of the canton, based on the bibliographic review of 2 pre-graduate documents and the Development and Land Management Plan of the province of Cotopaxi 2015 - 2025, which includes 10 Cultural Heritage Sites of the canton of Salcedo, The first objective was to establish a check list of tourist attractions, taking as a reference the last update of the inventory in 2021 and then using the methodology of the MINTUR, resulting in a total of 29 tourist attractions in the category of natural sites and cultural manifestations. The second objective was to establish a SWOT matrix based on the diagnosis of the canton's situation, and then relate it to the three MEFI - MEFE and MEFI MEFE matrices in order to analyze internal and external factors, which will allow strategies to be proposed in order to enhance strengths and take advantage of opportunities. In order to fulfill the second objective, the Sandoval (2006) potentiality evaluation methodology was used. The following results were obtained: San Miguel with High Potential, followed by Cusubamba, Panzaleo and Mulalillo with Medium Potential, and Mulliquindil, Antonio José Holguín with Low Potential. Finally, the third objective is the elaboration of an academic article in the format of the RENPYS magazine, where the research work is synthesized and disseminated within the academic environment. So that it will serve as a contribution tool for future research in the Salcedo canton.